2018
DOI: 10.1089/tmj.2017.0189
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Users with Suicidal Ideation on Sina Weibo

Abstract: Our findings may help to identify individuals with suicidal ideation who are not identified by the traditional clinical approach. Consequently, detecting and helping individuals who may be at risk of committing suicide may become more efficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…In this study, we identified 3039 PSI in a Chinese suicidal community on Weibo and explored their behavior in the community. The finding that the agglomeration behavior of these PSI compared with the findings from previous study (114 PSI detected from 1 million Weibo users [37]), highlights the importance of suicide prevention at community level. To the knowledge of the researchers, this is the first study to report the behavior of PSI at community level.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In this study, we identified 3039 PSI in a Chinese suicidal community on Weibo and explored their behavior in the community. The finding that the agglomeration behavior of these PSI compared with the findings from previous study (114 PSI detected from 1 million Weibo users [37]), highlights the importance of suicide prevention at community level. To the knowledge of the researchers, this is the first study to report the behavior of PSI at community level.…”
Section: Discussionmentioning
confidence: 51%
“…As PSI are very likely to tell others about their suicidal thoughts on Weibo, researchers are trying to detect and help PSI according to their postings on Weibo [36]. For example, by studying the postings PSI published on Weibo, Wang et al [37] were able to conclude that PSI are more active at night, and more women than men report their suicidal ideation. Some researchers explored the linguistic features of PSI on Weibo, and found that PSI may use less verbs, and post more words in their updates [38].…”
Section: Introductionmentioning
confidence: 99%
“…One study has found that public concern and engagement in protective behaviours increased when the threat of the H1N1 outbreak increased and decreasing when the perceived risk declined 29 . Second, content analysis of social networks posts will enable researchers to analyse human attitudes or reactions towards specific health hazards 30 . The data from social media may help identify individuals with anxiety or fears about infectious diseases who are not identified by the traditional clinical or survey approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The health care system was further overburdened as patients with mild symptoms sought hospitalization instead of self-isolation, mainly due to the anxiety and panic instigated by the epidemic [7]. After failing to be admitted to a hospital, patients sought help on Sina Weibo, a Chinese microblogging site similar to Twitter that allows people to communicate and share information instantly [8]. Social media has become an important channel for promoting risk communication during the crisis [9,10] and can be used to measure public attention given to public health emergencies [11], such as H7N9 [12][13][14], Ebola [9,[15][16][17][18][19], Zika virus [10,20,21], Middle East respiratory syndrome (MERS-CoV) [22], and Dengue fever [23].…”
Section: Introductionmentioning
confidence: 99%